Resource Efficient and Cleaner Production Assessment (RECP) in Pancoh Ecotourism Village, Regency of Sleman, Yogyakarta - Muhammad Dzulkifli; Nadhila Fitri Rahmi Harahap (Lasigo Akademia Indonesia, 2022)
This study aims to assess the Resource Efficiency and Cleaner Production (RECP) in tourism sector especially in Pancoh Ecotourism Village (PEV), Sleman. It assessed by using the RECP United Nations Industrial Development Organization (UNIDO) indicators for small and medium enterprise. It also used RECP assessment cycle method. The results show that there were two main activities that mostly use resources and energy in Pancoh Ecotourism Village (PEV), they are homestays and Pendopo. The use of energy in a homestay was bigger than in Pendopo. Also, inefficient use of energy and resources were found in homestays. The RECP recommendations for PEV were to use efficient stove, to use light-emitting diode (LED) lights and to attach magnets in the gas hose. If the PEV applied the recommendations, it has potential to reduce carbon by 22,535.68 CO2eq kg/year and it has potential to save IDR. 39,463,267/year. The indicators in RECP assessment for tourism village requires modifications since the pattern of resources and energy use in tourism villages is different from the small and medium enterprises that have implemented RECP method before